Allelopathy of aqueous extract from Caragana intermedia root on seven kinds of shrubs and herbs and its chemical component analysis - CHEN Lin; YANG Xinguo; SONG Naiping; ZHAI Deping; ZHAO Wei; LIU Xuedong (浙江大学学报. 农业与生命科学版)
Allelopathy played an important role in interspecific relationships of plants. Effects of aqueous extract from Caragana intermedia root on seed germination and seedling growth of plant species in desert steppe were investigated, to reveal the function of C. intermedia in artificial compound system and vegetation succession.Seven common species were selected, including Sophora alopecuroides, Astragalus adsurgens, Melilotus officinalis, Elymus dahuricus, Sorghum sudanense, Caragana korshinskii and Caragana microphylla. Laboratory bioassays were conducted, and gas chromatography-mass spectrometry (GC-MS) was used to analyze the compounds in the aqueous extract from C. intermedia root.The results showed that allelopathic effects were observed for aqueous extract from C. intermedia root, but showed distinct influences on different species. Seed germination and seedling growth of five species (S. alopecuroides, M. officinalis, S. sudanense, C. korshinskii and C. microphylla) were inhibited by aqueous extract at some certain concentrations; however, those of A. adsurgens and E. dahuricus were promoted. In addition, the aqueous extract from C. intermedia root had inhibition effect on seed germination of S. alopecuroides, S. sudanense and C. microphylla, whereas it had promotion effect on seedling growth at the same concentration. Twenty-one compounds were identified from the aqueous extract, including eight kinds of compounds such as alcohol, ketone, ether, ester, terpenes, organic acid, alkyl halide and nitrogen compounds.In sum, the aqueous extract from C. intermedia root has distinct allelopathic effects on different species in laboratory bioassays. Nevertheless, under the field condition, whether C. intermedia had allelopathic effects, and whether the action concentration could impose an allelopathic effect on seed germination and plant growth required further study.